2016
DOI: 10.1038/srep26764
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Resistive Switching in a Single Cu:7,7,8,8-tetracyanoquinodimethane Nanowire: A Promising Material for Resistive Random Access Memory

Abstract: We report a new type of sustained and reversible unipolar resistive switching in a nanowire device made from a single strand of Cu:7,7,8,8-tetracyanoquinodimethane (Cu:TCNQ) nanowire (diameter <100 nm) that shows high ON/OFF ratio (~103), low threshold voltage of switching (~3.5 V) and large cycling endurance (>103). This indicates a promising material for high density resistive random access memory (ReRAM) device integration. Switching is observed in Cu:TCNQ single nanowire devices with two different electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…23,24 The solid−gas interfacial reaction between neutral tetracyanoquinodimethane (TCNQ) (vapor) and the metallic Cu or Ag substrate (solid) resulted in the formation of a Cu-TCNQ or Ag-TCNQ layer whereby respective metals were getting oxidized (Cu(I) or Ag(I)) and TCNQ was reduced to the TCNQ monoanion. 25,26 Consistently, the oxidation of Cu or Ag was observed at the solid− liquid interface between metallic Cu or Ag and the TCNQ solution, generating a Cu-TCNQ or Ag-TCNQ thin film, respectively. 27,28 In the last two decades, chemical reactions at solid−liquid interfaces have emerged in order to functionalize metallic as well as semiconducting substrates with self-assembled and wellordered layers of CPs including metal−organic frameworks (MOFs) for various application possibilities (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…23,24 The solid−gas interfacial reaction between neutral tetracyanoquinodimethane (TCNQ) (vapor) and the metallic Cu or Ag substrate (solid) resulted in the formation of a Cu-TCNQ or Ag-TCNQ layer whereby respective metals were getting oxidized (Cu(I) or Ag(I)) and TCNQ was reduced to the TCNQ monoanion. 25,26 Consistently, the oxidation of Cu or Ag was observed at the solid− liquid interface between metallic Cu or Ag and the TCNQ solution, generating a Cu-TCNQ or Ag-TCNQ thin film, respectively. 27,28 In the last two decades, chemical reactions at solid−liquid interfaces have emerged in order to functionalize metallic as well as semiconducting substrates with self-assembled and wellordered layers of CPs including metal−organic frameworks (MOFs) for various application possibilities (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 68%
“…On-surface coordination chemistry has also been shown to be influenced by the redox activity of organic ligands. Tetrazine-based moieties are usually the most electron-deficient aromatic organic ligands, having a low-lying π* orbital due to the presence of sp 2 nitrogen (N) atoms . Upon exposing vapors of tetrazine derivatives to metallic platinum (Pt) or vanadium (V), on-surface oxidation was observed. , The bis­pyri­dinyl­tetra­zine ligand oxidized metallic Pt to Pt­(II) on the Au surface, and similarly, V was oxidized to V­(III) and V­(II) on the Au surface upon carrying out chemical reactions at the solid–gas interface involving metallic vanadium (V) and vapors of tetrazine derivatives (bis-pyrimid­inyl­tetrazine and bis-pyridinyl­tetrazine). , The solid–gas interfacial reaction between neutral tetracyanoquinodimethane (TCNQ) (vapor) and the metallic Cu or Ag substrate (solid) resulted in the formation of a Cu-TCNQ or Ag-TCNQ layer whereby respective metals were getting oxidized (Cu­(I) or Ag­(I)) and TCNQ was reduced to the TCNQ monoanion. , Consistently, the oxidation of Cu or Ag was observed at the solid–liquid interface between metallic Cu or Ag and the TCNQ solution, generating a Cu-TCNQ or Ag-TCNQ thin film, respectively. , …”
Section: Introductionmentioning
confidence: 99%
“…Using the value of the known parameters, we obtain C i = 2.83 × 10 –4 F/m 2 . The single NW device shows a room temperature mobility, μ ≈ 1.2 × 10 4 cm 2 V –1 s –1 measured on different devices, which is much higher than other CT complex materials ,,, and probably highest mobility in the organic FET family reported to date. , Table summarizes some high-mobility organic materials having mobility of >1. Although the on/off ratio is comparatively low ,,, in Cu:TCNQ, it shows extensively high mobility due to the material property as well as constrained dimension (lower diameter and shorter length) of the NWDUT.…”
Section: Resultsmentioning
confidence: 87%
“…Cu:TCNQ is a highly conducting polymeric material (σ ≈ 3 × 10 2 S/cm) at room temperature and can show significant nonlinear conductivity that even leads to charge density wave (CDW) transition at low temperatures . This material also has considerable interest for its electrical resistive state switching, ,, applications as conducting electrodes, , and excellent optoelectronic properties as a high responsive optical detector even in a single NW. , We have also used floating back gate device architecture to reduce leakage current. The device so fabricated allows us to measure the mobility in a single NW.…”
Section: Introductionmentioning
confidence: 99%
“…This can be an additional or alternate factor to the more accepted model that relates the switching behavior to the CuTCNQ interface. Basori et al, 40 using a simple metal-semiconductor-metal device model, found that the switching occurs primarily due to a lowering of the contact barrier at the cathode (the reversed bias junction) with an additional contribution arising from a lowering of the resistance of the CuTCNQ, although with less effect. The lowering of the contact potential agrees well with the qualitative mechanisms suggested before, where the formation of Cu filaments at the contacts has been suggested as the cause of switching.…”
Section: The Mtcnq Electronic Structurementioning
confidence: 99%